Sliding Mode Control for Permanent Magnet Synchronous Motor Drive Based on an Improved Exponential Reaching Law - Aimeng Wang (IEEE Access, 2019)
Permanent magnet synchronous motor (PMSM) is a typical nonlinear and multi-variable coupled system, which is sensitive to the uncertainty or variations in the motor parameters and the external disturbance which lead to the deterioration of the steady-state performance. Therefore, it is necessary to introduce effective control methods to improve the drive quality. In this paper, the DQ-axes inductances considering the magnetic saturation of the PMSM which has a significant influence on the operating characteristics are obtained, and the variable parameters are substituted into the control system. Then, a novel sliding mode control strategy is analyzed and adopted. An improved exponential reaching law is proposed in order to solve the chattering problem and improve the performance, which is verified by the theory and simulation. It demonstrates the smooth and quick responses using the new approach can be achieved to enhance the robustness of the drive system compared with conventional sliding mode control method.